Antecedents of unfinished nursing care: a systematic review of the literature - Chiappinotto, Stefania; Papastavrou, Evridiki; Efstathiou, Georgios; Andreou, Panayiota; Stemmer, Renate; Ströhm, Christina; Schubert, Maria; De Wolf-Linder, Susanne; Longhini, Jessica; Palese, Alvisa (My University, 2022)
Background Unfinished Nursing Care (UNC) concept, that express the condition when nurses are forced to delay or omit required nursing care, has been largely investigated as tasks left undone, missed care, and implicit rationing of nursing care. However, no summary of the available evidence regarding UNC antecedents has been published. The aim of this study is to identify and summarise antecedents of UNC as documented in primary studies to date. Methods A systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines was conducted. MEDLINE, CINAHL, SCOPUS, and PROSPERO databases were searched for quantitative studies reporting the relationships between antecedents and UNC published after 2004 up to 21 January 2020. The reference lists of secondary studies have been scrutinised to identify additional studies. Two reviewers independently identified studies and evaluated them for their eligibility and disagreements were resolved by the research team. The quality appraisal was based on the Joanna Briggs Institute Critical Appraisal tools, according to the study designs. A data extraction grid was piloted and then used to extract data. The antecedents that emerged were thematically categorised with an inductive approach. Results Fifty-eight studies were included; among them, 54 were cross-sectional, three were cohort studies, and one was a quasi-experimental study. They were conducted mainly in the United States and in hospital settings. The UNC antecedents have been investigated to date at the (a) unit (e.g., workloads, non-nursing tasks), (b) nurse (e.g., age, gender), and (c) patient levels (clinical instability). Conclusions At the unit level, it is highly recommended to provide an adequate staff level, strategies to deal with unpredictable workloads, and to promote good practice environments to reduce or minimise UNC. By contrast, at the nurse and patient levels, there were no clear trends regarding modifiable factors that could decrease the occurrence of UNC. The map of antecedents that emerged can be used to design interventional studies aimed at changing research from merely descriptive to that which evaluates the effectiveness of interventions.
Keywords: Antecedents; Factors; Implicit of nursing care; Missed nursing care; Predictors; Reasons; Systematic review; Tasks left undone; Unfinished nursing care